Direct energy deposition (DED) process parameters optimization via experiments (C) - Mohamed Zaki Bin Mohamed Abdul Kadir (Nanyang Technological University, 2024)
Direct Energy Deposition (DED) is a transformative method in Additive Manufacturing that allows for the precise fabrication of complex metal structures. Originating as a tool for repairing and modifying components, DED technology has evolved to play a pivotal role in a variety of industries, thanks to its ability to create intricate geometries and functional gradient materials. Due to this, there exist a problem in optimizing the parameters to get the right specifications. The primary goal of this study is to systematically investigate how various process parameters influence the properties of the manufactured samples. This involves a thorough experimental analysis to determine the effect of these variables on the deposition process. Finally, the project aims to establish a recommended range of parameters for singletrack deposition in DED, offering a guideline for optimal printing conditions. This conclusion is drawn from the extensive analysis of the experimental results. The report concludes by highlighting the significance of these findings for advancing the capabilities and understanding of DED, proposing valuable insights for future research.